Identifikasi Terjadinya Liquid Loading Dimasa Yang Akan Datang Dengan Metode Turner Pada Sumur X Lapangan Donggi Matindok - Moh Fuzan Yasin; M. Ardian Pratama; Engeline Marlin; Fatma; Nijusiho Manik; Muhammad Rizki; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Well X is one of the gas wells owned by PT Pertamina EP Cepu Donggi Matindok Field, with the ongoing gas production process, the reservoir experiences a decrease in pressure over time which affects the productivity of the well so that the production rate of the well can decrease. In conditions where the pressure continues to decrease, it will cause the flow rate to no longer be able to lift the fluid, this is called liquid loading.The purpose of this study is to analyze and calculate the minimum flow rate and calculate the future IPR. The problem limitation in this study is emphasized on the analysis of well X to determine the minimum flow rate value and the minimum flow rate value when there is a decrease in pressure in the well. The method used is the Turner method in calculating the critical flow rate and the LIT calculation method in calculating the future IPR to determine the shape of the IPR curve in the future. The results of the calculation of the minimum flow rate of well X vary depending on the size of the Casing or tubing through which the fluid passes, at 7"Casing of 11.64 MMscfd, at 4.5" Casing of 4.87 MMscfd, and 3.5" tubing of 2.5 MMscfd. Based on the results of the IPR curve correlation with OPR using commercial software, using a choke size of 0.5625 inches with the actual flow rate obtained of 12.38 MMscfd.